STUDI KOMPARATIF IDIOM WARNA DALAM BAHASA INDONESIA DAN BAHASA INGGRIS SERTA PEMANFAATANNYA SEBAGAI BAHAN AJAR BIPA - Fatma Anggita Putri, - (2022)
This research based on the difficulties experienced by BIPA students when learning Indonesian. They have difficulty to understand the meaning of Indonesian idioms. They tried to translate idioms grammatically and literally into their mother tongue language that is, English. However, idioms can not be translated grammatically and literally, so they failed to understand. This study aims to explain and describe the form, meaning of idioms, as well as differences and similarities found in Indonesian idioms and English idioms as teaching materials for Indonesian Language for Foreign Speakers (BIPA) on BIPA 4/B2/intermediate level. The research method used in this study is a qualitative method. This study uses a comparative study to systematically describe the phenomenon of differences and similarities of Indonesian idioms and English idioms. Data collection techniques that are used in this study are interview, reading-note, idiom cards, and validation sheets which were assessed by linguists and BIPA experts. The findings in this study are Indonesian idioms with 22 red idioms, 9 yellow idioms, 2 blue idioms, 32 black idioms, 33 white idioms, English idioms with 24 red idioms, 4 yellow idioms, 30 blue idioms, 28 black idioms, 16 white idioms. The total data for Indonesian idioms are 98 idioms, while there are 102 English idioms. Indonesian idioms are also found in the form of complex words consisting of affixation and reduplication. Indonesian and English idioms have similarities in idioms forms based on word class, namely noun idioms, adjective idioms, adverb idioms, and prepositional idioms. In addition, this study also shows that Indonesian and English have similarities in their constituent elements and differences in the meaning of idioms. Indonesian idiom data and the results of the analysis can be used as teaching materials and as an introduction to Indonesian culture through idiom learning as a support for BIPA idiom learning.